Chemical and Physical Quality, Fermentation Characteristics, Aerobic Stability, and Ruminal Degradability of Sorghum Silage Inoculated with Lactiplantibacillus plantarum and Limosilactobacillus fermentum - Fitriani, D.; Ardiansyah, M.; Kurniawati, A.; Bachruddin, Z.; Paradhipta, D. H. V. (Faculty of Animal Science, IPB University, 2024)
This study was carried out to determine the effect of homo (Lactiplantibacillus plantarum FNCC 0020) and hetero (Limosilactobacillus fermentum BN21) fermentative lactic acid bacteria on chemical compositions, fermentation characteristics, aerobic stability, and ruminal digestibility of sorghum (Sorghum bicolor L. Moench) silage. The sorghum forage was harvested at the milk ripening phase with a dry matter content of 25.6% and fermented for 100 days with different inoculants: treatments without inoculant (CON), L. plantarum (LP), L. fermentum (LF) as well as a mixture of LP and LF at a ratio of 1:1 (MIX). The experiment was conducted using a completely randomized design with 5 replications per treatment, and all inoculants were applied at 105 cfu/g of fresh forage. The results showed that LF silage caused a 66.3% reduction in cyanide acid content, the lowest mold count, and longer aerobic stability compared to LP and CON. The lowest pH (p<0.05) and highest organic matter digestibility (p<0.05) were obtained on LP silage, while the CON silage showed no significant difference. The LP and LF silage showed the highest total volatile fatty acid (p<0.05), while there was no significant between CON and others. The LF silage had the highest acetate and the lowest propionate (p<0.05). These results showed that L. fermentum was more effective in decreasing cyanide acid content and increasing the aerobic stability of sorghum silage, while L. plantarum was able to lower pH and reduce ammonia concentration.